Gutai bijutsu kyokai e dansaekhwa: a situação da pintura abstrata no Leste Asiático do pós-guerra - Bonani, João Víctor Kurohiji [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Important gestures within modern and contemporary art practices of East Asian art, the early works by the Japanese group Gutai Bijutsu Kyōkai (1954-1957) and the paintings by the South Korean Dansaekhwa movement during the 1970s are often liable of being inserted in comparative stylistic models that marginalize them within a dominant western art history, configuring as limiting processes of understanding applied to local artistic practices in relation to a global and hegemonic art. Thus, starting from the continuing need for new, critical and dialogical perspectives that discuss these works in their complexities and unprecedented articulations, as well as the emerging worldwide interest in these groups of artists and the scarcity of national research on the subject, the research uses primary documents by artists and critics, such as the Gutai group art manifesto (1956) written by Yoshihara Jirō, and theorists such as Barbara Rose (1980), Clement Greenberg (1997), Dora Vallier (1986), Joan Kee (2003, 2013), John Clark (2014), Ming Tiampo (2011, 2013) and Moacir dos Anjos (2015) to promote a dialogue between the movements through comparative analysis and image analysis in order to distinguish their own historical-cultural and formal complexities, without first ignoring their relationship to western abstract trends. Consequently, it is verified that these groups, in response to global and local antecedents, and in reaction to their historical-cultural contexts, have developed their own practices within the history of abstract art. While the Gutai group presented itself as a group of artists with a strong collective spirit, the Dansaekhwa painters formed a less cohesive group, united by critics and institutions. Both arise in the context of the Post War (1939-1945) and Korean Post War (1950-1953)... (Complete abstract electronic access below)

Frutos de importantes gestos dentro das práticas artísticas modernas e contemporâneas da arte do Leste Asiático, as obras do período inicial do grupo japonês Gutai Bijutsu Kyōkai (1954-1957) e as pinturas do movimento sul-coreano Dansaekhwa, durante a década de 1970, são frequentemente passíveis de serem inseridas em modelos estilísticos comparativos que as marginalizam dentro de uma história da arte ocidental dominante, configurando-se como processos limitantes de entendimento aplicados às práticas artísticas locais em relação a uma arte global e hegemônica. Dessa forma, partindo da necessidade contínua de novos olhares, críticos e dialógicos, que discutam essas obras em suas complexidades e articulações inéditas, bem como do emergente interesse mundial por esses grupos de artistas e da escassez de pesquisas nacionais sobre os movimentos, a pesquisa utiliza documentos primários de artistas e de críticos, como o manifesto de arte do grupo Gutai (1956), escrito por Yoshihara Jirō, e teóricos como Barbara Rose (1980), Clement Greenberg (1997), Dora Vallier (1986), Joan Kee (2003, 2013), John Clark (2014), Ming Tiampo (2011, 2013) e Moacir dos Anjos (2015) para promover um diálogo entre os movimentos, através de análise comparativa e análises de imagens, a fim de distinguir suas próprias complexidades histórico-culturais e formais, sem antes ignorar suas relações com as tendências abstratas ocidentais. Consequentemente, verifica-se que estes grupos, em resposta aos antecedentes globais e locais, e em reação aos seus contextos histórico-culturais, desenvolveram práticas próprias dentro da história da arte abstrata. Enquanto o grupo Gutai apresentava-se como um grupo de artistas de forte espírito coletivo, os pintores do Dansaekhwa formaram um grupo menos coeso, unido pelos críticos e instituições... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Artes - Ásia, Leste - Séc. XX; Pintores; Pintura abstrata; Arts